Progressive Hearing Loss in Early Childhood. Issue 5 (September 2016) - Barreira-Nielsen, Carmen; Fitzpatrick, Elizabeth; Hashem, Serena; Whittingham, JoAnne; Barrowman, Nicholas; Aglipay, Mary
Abstract : Objectives: Deterioration in hearing thresholds in children is of concern due to the effect on language development. Before universal newborn hearing screening (UNHS), accurate information on the progression of hearing loss was difficult to obtain due to limited information on hearing loss onset. The objective of this population-based study was to document the proportion of children who experienced progressive loss in a cohort followed through a UNHS program in one region of Canada. We explored risk factors for progression including risk indicators, audiologic, and clinical characteristics of children. We also investigated deterioration in hearing as a function of age. For this study, two working definitions of progressive hearing loss were adopted: (1) a change of ≥20 dB in the 3 frequencies (500, 1000, and 2000 Hz) pure-tone average, and (2) a decrease of ≥10 dB at two or more adjacent frequencies between 500 and 4000 Hz or a decrease in 15 dB at one octave frequency in the same frequency range. Design: Population-based data were collected prospectively on a cohort of children identified from 2003 to 2013 after the implementation of UNHS. Clinical characteristics including risk indicators (as per Joint Committee on Infant Hearing), age at diagnosis, type and severity of hearing loss, and initial audiologic information were recorded when children were first identified with hearing loss. Serial audiometric results were extracted from the medical charts for this study. Differences between children with progressive and stable hearing loss were explored using χ 2 tests. Association between risk indicators and progressive hearing loss was assessed through logistic regression. The cumulative amount of deterioration in hearing from 1 to 4 years of age was also examined. Results: Our analysis of 330 children (251 exposed to screening) with detailed audiologic records showed that 158 (47.9%) children had some deterioration (at least ≥10 dB and) in hearing thresholds in at least one ear. The 158 children included 76 (48.1%) with ≥20 dB loss in pure-tone average in at least one ear and 82 (51.9%) with less deterioration in hearing levels (≥10 but <20 dB). In the children with progressive hearing loss, of 131 children initially diagnosed with bilateral loss, 75 (57.3%) experienced deterioration in 1 ear and 56 (112 ears; 42.7%) in both ears (total of 187 ears). Of 27 children with an initial diagnosis of unilateral loss, 25 experienced deterioration in the impaired ear and 5 in the normal-hearing ear, progressing to bilateral hearing loss. Within 4 years after diagnosis, the mean decrease in hearing for children with progressive loss was 25.9 dB (SD: 16.4) in the right ear and 28.3 dB (SD: 12.9) in the left ear. We explored the risk factors for hearing loss identified by Joint Committee on Infant Hearing where there were sufficient numbers in our sample. On multivariate analysis, there was no statistically significant relationship between most risk indicators examined (neonatal intensive care unit admission, family history, syndromes, and postnatal infections) and the likelihood of progressive loss. However, the presence of craniofacial anomalies was inversely associated with risk of progressive hearing loss (odds ratio = 0.27; 95% confidence interval: 0.10, 0.71; p = 0.01), that is, these children were more likely to have stable hearing. Conclusions: Given that almost half of the children in this cohort experienced deterioration in hearing, close postneonatal monitoring of hearing following early hearing loss identification is essential to ensure optimal amplification and therapy. Abstract : Children with permanent hearing loss are considered at risk for deterioration in hearing and surveillance is recommended for children with risk indicators. Little is known about the proportion of children who experience progressive hearing loss or the characteristics of affected children. This report provides population-based data on an 11-year newborn hearing screening cohort to document progressive hearing loss in young children. We also explored the relationship between risk indicators and progressive loss as well as the extent of deterioration in hearing over time.